2010
DOI: 10.5511/plantbiotechnology.27.141
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gene for Dioscorea batatas tuber lectin 1 in transgenic tobacco confers resistance to green-peach aphid

Abstract: Dioscorea batatas tuber lectin 1 (DB1) is a storage protein isolated from yam tuber, and is shown to be a mannose-binding lectin. It has 58% amino-acid identity to insecticidal snowdrop bulb lectin GNA. In this study, we demonstrated that Ն1 mg ml Ϫ1 DB1 in an artificial diet significantly decreased the survival and fecundity of green peach aphid, Myzus persicaeca. We produced transgenic tobacco plants expressing cDNA of DB1 under the control of Cauliflower mosaic virus 35S promoter (35S-DB1) or phloem-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It was also reported that transgenic crops expressing garlic lectins (ASA and ASAL) could confer resistance against various lepidopteran and homopteran insects, viz., Nilaparvata lugens , Nephotettix virescens , Sogatella furcifera, Spodoptera littoralis , Lipaphis erysimi and Aphis craccivora [8], [17], [29]-[31]. Further, it was reported that the expression of Dioscorea batatas tuber lectin in rice and tobacco reduced the survival of BPH and aphid by 30% and 60%, respectively [32], [33]. Garlic lectins serve as promising candidate molecules for the development of transgenic crops against sucking pests as they are from edible source, and as such may not pose any biosafety problem.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that transgenic crops expressing garlic lectins (ASA and ASAL) could confer resistance against various lepidopteran and homopteran insects, viz., Nilaparvata lugens , Nephotettix virescens , Sogatella furcifera, Spodoptera littoralis , Lipaphis erysimi and Aphis craccivora [8], [17], [29]-[31]. Further, it was reported that the expression of Dioscorea batatas tuber lectin in rice and tobacco reduced the survival of BPH and aphid by 30% and 60%, respectively [32], [33]. Garlic lectins serve as promising candidate molecules for the development of transgenic crops against sucking pests as they are from edible source, and as such may not pose any biosafety problem.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of adults emerging from pupae was reduced to 33%, when fed on 0.01% (w/v) DB1 in an artificial diet (Ohizumi et al 2009). We also demonstrated that ≥1 mg/ml DB1 in an artificial diet significantly decreased the survival and fecundity of green peach aphid, Myzus persicaeca (Kato et al 2010). The number of survival aphids was reduced to 60% in transgenic tobacco expressing cDNA of DB1 under the control of Note DOI: 10.5511/plantbiotechnology.12.0726b…”
mentioning
confidence: 82%
“…AB513659) and the rice sucrose synthase-1 (RSs1) promoter (accession no. AJ401233; Shi et al 1994) were obtained as described in Kato et al (2010). The terminator of RSs1 was PCR cloned using RSs1ter-1s primer (5′-TAA TGG AGG GGA AAA TAT GCA TCT TCA GCA GG-3′) and RSs1ter-2a-Sac primer (5′-GAGCTCATC TAC TAC AGC AGT AGA AAA GAT GCA ACC-3′; SacI site is underlined) and connected to the 3′end of the DB1 cDNA by blunt ligation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, M. persicae feeding on the transgenic plants producing the dsRNAs or siRNA of salivary proteins MpC002 , MpPIntO1 , and MpPIntO2 ; receptor of activated kinase C gene MpRack1 [46,61,151]; serine protease ( MySP ) [62]; Acetylcholinesterase 2 gene MpAChE2 ; V-ATPase E ; 40S ribosomal protein S5-like isoform-1 Rps5 ; SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily D member 1-like gene SMARCD1 ; tubulin folding cofactor D gene TBCD ; mediator complex subunit 31 Med31 ; ribosomal protein S14 Rps14 [63], hb [64], MpMIF1 [59] and Aquaporin gene MpAQP1 ; sucrase gene MpSUC1 ; and sugar transporter gene MpSt4 [65], resulted in significant reduction in the target gene expression and reduced fecundity. Aside from plant-mediated silencing, several cases in which plants expressing lectins for controlling M. persicae were reported and those include Galanthus nivalis agglutinin, GNA expressing tobacco and potato plants [66,67], Allium sativum leaf lectin, ASAL [68], Allium cepa agglutinin, ACA expressing mustard [69], Pinellia ternate agglutinin, PTA expressing tobacco plants [70,152], Dioscorea batatas tuber lectin 1, DB1 [71], legume lectins: ConA expressing potato plants [72], Jacalins: Helianthus tuberosus agglutinin, HTA expressing tobacco plants [73] and NICTABA -related lectin, AtPP2 expressing in Arabidopsis [74], all showed significant insecticidal activity against M. persicae .…”
Section: Rnai-based Approaches For the Control Of Insect Vectorsmentioning
confidence: 99%